1996
DOI: 10.1080/00071669608417905
|View full text |Cite
|
Sign up to set email alerts
|

Selection for egg shell strength in laying hens using shell membrane characteristics

Abstract: 1. Divergent selection for attachment strength between the shell membrane and the calcium shell was performed in a White Leghorn strain. Multivariate analysis was used to estimate genetic parameters for shell membrane measurements and shell thickness. The aim was to investigate the possibility of improving shell strength in laying hens by selecting for increased attachment strength. 2. A significant direct selection response for attachment strength was achieved. There was a favourable correlated selection diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Farzin et al (2006) reported a heritability estimate for shell thickness of 0Á68 in laying hens. This coincides with the results from the present study, but both estimates are higher than the heritability of 0Á33 reported by Johansson et al (1996). The h 2 estimates for WL21 and WL35 corresponded with findings from Brand et al (2009).…”
Section: Discussionsupporting
confidence: 92%
“…Farzin et al (2006) reported a heritability estimate for shell thickness of 0Á68 in laying hens. This coincides with the results from the present study, but both estimates are higher than the heritability of 0Á33 reported by Johansson et al (1996). The h 2 estimates for WL21 and WL35 corresponded with findings from Brand et al (2009).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the correlations between shortening force at fracture of egg, strength of eggshell and ratio of cracked eggs, eggs without shell and abnormal eggs to total number of eggs were negative, too. Thus, testing of shortening force at fracture and strength of eggshell can be used (in agreement with JOHANSSON et al, 1996) in selection for egg quality within laying lines on hens.…”
Section: Discussionmentioning
confidence: 94%
“…On the contrary, BRAH et al (1992) found no significant antagonistic relationship with body weight, egg number and egg weight. JOHANSSON et al (1996) studied the possibility of increase of eggshell strength by means of selection. They carried out divergent selection for attachment strength and they suggested the possibility of improving shell strength in laying hens by selecting for increased attachment strength.…”
Section: Zusammenfassungmentioning
confidence: 99%
“…(9) and Zhang et al(39) in the different breeds. Johansson et al(12) and Besbes and Gibson (8) estimated heritability as moderate to high values (0.23 to 0.41) for egg shape index. A moderate heritability estimation (0.33) for shape index was consistent with the estimates reported by Johansson et al(12) andBesbes and Gibson (8).…”
mentioning
confidence: 99%